Old Literary Tibetan : A Comperehensive Text Grammar Based on the Old Tibetan Annals - Bialek, Joanna (Language and Linguistics E-Books Online, Collection 2025., 2026)
Old Literary Tibetan: A Comprehensive Grammatical Description Based on the "Old Tibetan Annals" is a pioneering work in the field of Tibetan written languages, offering unprecedented insights into the earliest documented Tibetic language and one of the earliest written Trans-Himalayan languages. Opening the gate to the oldest preserved Tibetan literature, the book is of great value not only for Tibetologists, but also for linguists thanks to its immense contributions to Trans-Himalayan lingusitics. Bialek's landmark description of Old Literary Tibetan will be highly valuable in future descriptive and analytical work of other Trans-Himalayan languages, the study of which will undoubtedly substantially benefit from the publication of the grammar.